2005
DOI: 10.1056/nejmoa043526
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin for the Secondary Prevention of Coronary Events

Abstract: A one-year course of weekly azithromycin did not alter the risk of cardiac events among patients with stable coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
168
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(180 citation statements)
references
References 25 publications
2
168
0
10
Order By: Relevance
“…Although other evidence implicates infections and the immune system in cardiovascular disease [19,35,36], the negative findings of two randomized-controlled trials of antibiotic administration [37,38] suggest that bacterial infection is not likely involved in circulatory disease. The somewhat high (albeit nonsignificant) risks for hypertensive heart disease and CeVD if RBM dose is used (Table 6) (weakly) suggest that dose to this tissue may not be relevant for these endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Although other evidence implicates infections and the immune system in cardiovascular disease [19,35,36], the negative findings of two randomized-controlled trials of antibiotic administration [37,38] suggest that bacterial infection is not likely involved in circulatory disease. The somewhat high (albeit nonsignificant) risks for hypertensive heart disease and CeVD if RBM dose is used (Table 6) (weakly) suggest that dose to this tissue may not be relevant for these endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…11 Trials of antibiotics, however, have not shown benefit in lowering the risk of recurrent coronary events. 12,13 Similarly, treatments aimed at eliminating or controlling chronic infections have not proven to be helpful for the prevention of stroke. 10 Inflammatory biomarkers such as high-sensitivity C-reactive protein and lipoproteinassociated phospholipase A2 are also independently associated with cardiovascular and stroke risk.…”
mentioning
confidence: 99%
“…WIZARD (Weekly Intervention with Zithromax for Atherosclerosis and Related Disorder) study 24 failed to find a long term benefit of administering Azithromycin for individuals with stable coronary artery disease, serologic evidence of C. Pneumoniae and past history of myocardial infarction. The ineffectiveness of antibiotics for prevention of secondary cardiovascular events has also been shown in ACES, 25 PROVE IT-TIMI 26 and AZACS 27 trials. But STAMINA 28 trial found that antibiotic treatment significantly reduces adverse cardiac events in patients with acute coronary syndromes, but this was independent of H. pylori or C. pneumoniae seropositivity.…”
Section: Discussionmentioning
confidence: 86%